Surgical management of intestinal failure; Initial experiences from an intestinal failure, rehabilitation and transplant unit in Iran - Nikoupour, Hamed (2021)
Background: Intestinal failure (IF) is a life-threatening medical condition. The management of IF in low- and middle-income countries without home parenteral nutrition (HPN) remains unclear. We recently established an intestinal rehabilitation unit (IRU) and aimed to provide our experience on the current management and outcomes of IF in Iran. Methods: In this cross-sectional case series, data were collected from an established database on IF in the Shiraz Transplant Center in Abu Ali Sina hospital, affiliated to Shiraz University of Medical Sciences, Iran from January 2018 to October 2018. Results: Overall, 30 patients with a mean age of 44.13 ± 10.32 years, which included 25 males, were recruited. Short bowel syndrome (SBS) (60%) and enterocutaneous fistulae (27%), as complication of previous surgeries, were the main causes of IF. The most common type of IF was type 3 (67 %). Mesenteric ischemia was the leading mechanism of IF (47%). Fifteen patients (50%) received autologous gastrointestinal reconstruction surgery (AGIRS), and two (7%) patients had serial transverse enteroplasty (STEP). At the end of follow-up, 15 patients recovered from IF (50%). The overall survival rate was 83.3%. Conclusion: This series introduced the results of a multidisciplinary program for the treatment of IF in a middle-income country that lacks facilities for HPN. Our protocol of care, understanding the need for development of HPN, showed promising clinical outcomes.